Faktor-Faktor yang Mempengaruhi Pencegahan Fraud - Satria Wibawa; Haryono Umar (Sekolah Pascasarjana Perbanas Jakarta, 2022)
The purpose of this research was to determine effect of reward, punishment and work environment on fraud precaution/prevention. Quantitative.method and multiple regression analysis are used on this research, The population observed was the environment and colleagues of the researchers. 58 respondents are selected who met the criteria. The results of this research is different from the research conducted by Rosmita Dewi Yuniarti and Nur Apandi (2011), and Shanikat, Mohammed, et. al., (2014) with the results that punishment and reward are factors that have a positive effect on prevention of fraud. This research reveals that reward has a significantly influence prevention of fraud, punishment does not effect prevention of fraud, environment of work.has significant effect on fraud prevention, and then reward, punishment, and environment of work are simultaneously have significant effect;on’ prevention of fraud,.